AI-powered chatbots for pharmacy-based patient education and counseling - Pal, Tarun; Chandrakar, Kunal (Journal of Neonatal Surgery, 2025)
The increasing demand and use of technology has led to the convergence of technology with health and diagnostic procedures. Digital health is the use of technology and information to enhance and alleviate health issues, as the name suggests. The Indian healthcare industry is changing as a result of wearable technology, telemedicine, genomics, virtual reality (VR), robotics, and artificial intelligence (AI). India is poised for a "digital health" revolution, much like many other economies. (Digital Health Report, 2020: Informa Markets' Indian Health). The use of digital health technologies has become essential to the provision of healthcare. The health technology sector, which includes wearables, telemedicine, e-pharmacies, and other products, has grown recently all over the world. Additionally, a lot of research and development has gone into integrating technology like blockchain, virtual reality, robots, and artificial intelligence with medications and healthcare. Healthcare is the biggest industry in India and has a lot of room to grow. This market is driven by the modern world's increasing need for digital healthcare solutions.